Sanksi Bagi Notaris Yang Mempromosikan Jabatannya Pada Sosial Media - Njoto, Meishell (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2019)
Notary plays an important role in making authentic deed in Indonesia. Notaries are often referred to occupying honorary positions as general or state officials. As the holder of an honorary position trusted by the public to make an authentic deed, the Notary must comply with the applicable laws and the Code of Ethics. Obligations and prohibitions of Notaries have clearly been regulated in UUJN and Notary Ethics Code, but that does not mean there are no Notaries who violate these rules. In order to find out what the legal consequences of a notary who violated social media promotion, the authors conducted this research. The research method used in this study is normative legal research. Normative legal research is legal research conducted by examining materials derived from various laws and regulations and other materials from various literatures. Which means this research examines secondary data material or does a literature review. The approach used in this study is the statutory approach and the conceptual approach. The result of this research is the prohibition on promotion through social media which actually has been regulated in various rules regarding notaries along with the legal consequences if the Notary Public violates these rules.